Analysis of the Background and the Political, Social, and Cultural Context in Which the 1824 Constitution and the Constitutive Act of the Mexican Federation Were Created - Hernández Gómez, Luis Gustavo; Hernández Hernández, Miguel Armando (Revista Internacional & Comparada de Derechos Humanos, 2024)
The 19th century was a period marked by profound political and social changes in both Europe and the Americas. This context of global transformation decisively influenced the birth of new constitutions, such as Mexico’s in 1824 and its Constitutive Act of the Mexican Federation. These fundamental norms emerged as a response to the crises of the old colonial regime and reflected the aspirations for freedom and equality that permeated the political environment. Through this essay, which we had the opportunity to write, we focus on analyzing the historical and legal background that gave rise to the 1824 Constitution, considering key influences such as the 1812 Constitution of Cádiz and the 1787 United States Constitution. This comparative analysis will allow us to understand how foreign models were adapted to the Mexican reality, marked by deep social and regional divisions and an emerging search for national identity. It is also important to emphasize that, within the discussions of the time, the role of Miguel Ramos Arizpe was fundamental, since his influence on the creation of the federal system sought to balance power between the states and the central government. Along the same lines, we also revisit the mythical “Discurso de la profecía,” where Fray Servando Teresa de Mier made warnings about federalism and its impact on independent Mexico. The purpose of reading this essay is to offer a critical vision of how these foundational documents sought to build a sovereign nation, uniting tradition and modernity, and how they responded to the political and social challenges of their time.